A new technique to determine vertical dimension of occlusion from anthropometric measurements of fingers - Ruchi Ladda; Aruna J Bhandari; Vikrant O Kasat; Gangadhar S Angadi (Wolters Kluwer Medknow Publications, 2013)
Purpose: The purpose of this study was to find the correlation between vertical dimension of occlusion (VDO) and length of fingers. Materials and Methods: A cross-sectional study was conducted on 400 dentate subjects comprising of 200 males and 200 females. Anthropometric measurements of VDO, length of index finger, length of little finger, and distance from tip of thumb to tip of index finger of right hand were recorded clinically using modified digital vernier caliper. Correlation between VDO and length of fingers was studied using Spearman's coefficient. For the execution of regression command and preparation of prediction equations to estimate VDO, Statistical Package for Social Sciences Software Version 11.5 was used. Results: VDO was significantly and positively correlated with all the parameters studied. In males, correlation of VDO was strongest for length of index finger (r-0.406) whereas in females, it was strongest for length of little finger (r-0.385). VDO estimation using regression equation had a standard error of ± 3.76 in males and ± 2.86 in females for length of index finger, ±3.81 and ± 2.74 in males and females respectively for length of little finger, ±3.99 and ± 2.89 in males and females respectively for distance from tip of thumb to tip of index finger. Conclusions: Since the variations between VDO and finger lengths are within the range of 2-4 mm, VDO prediction through this method is reliable, and reproducible. Also the method is simple, economic, and non-invasive; hence, it could be recommended for everyday practice.